Hubungan Karakteristik Responden Dengan Pelaksanaan Pencegahan Infeksi Nifas Oleh Bidan di UPTD Puskesmas Mompang Kecamatan Panyabungan Kabupaten Mandailing - Anni Hidayah1; Sinuhaji, Lidya Natalia; Nur Aini; Nirmala Devi; Nur Safitri; Melia Ningsih (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
Puerperal infection is an infection - inflammation of all genital organs during the puerperium for any reason, provided that the increase in body temperature exceeds 38oC without counting the first day and consecutively for 2 days. One of the causes of puerperal infection is the manipulation of the helper: too often internal inspection, the tools used are less clean than pests. 2021. Purpose: This type of research is descriptive correlative with a cross sectional approach. This research was conducted from February to May 2021. Method: Researchers used a totaly sampling technique. Analysis of the data used chi - square. Result: Based on the results of the study, of the 40 respondents the majority aged between 22-39 years were 23 people (57.5%), education D I Midwifery were 22 people (55%), work experience 14-26 years were 27 people (67.5 % ), and less knowledgeable as many as 24 people ( 60% ). From the results of data analysis of the relationship between age and the implementation of puerperal infection prevention, p = 0.002 and OR = 11.40, it means that there is a significant relationship. Education with the implementation of puerperal infection prevention obtained p value = 0.032 and OR = 5.343 meaning that there was a significant relationship and work experience with the implementation of puerperal infection prevention obtained p = 0.063 and OR = 5.923 meaning there was no significant relationship. Conclusion: From the results of this study, it is hoped that midwives as health workers will improve their experience, knowledge, and quality of service in preventing puerperal infections.